Transfusion-transmitted occult hepatitis B virus infection: current understanding, challenges, and its implication in blood safety - Huang, Linbin; He, Baoren; Mo, Qiuhong; Li, Bin; Yan, Xipeng; Lai, Rongji; Wang, Xinwei; Li, Jinlian; Lai, Mingshuang; Xie, He; Sun, Jujun; Ye, Xianlin; et al. (Frontiers in Immunology, 2025)
Occult hepatitis B virus infection (OBI) represents a specific form of hepatitis B virus (HBV)infection characterized by the presence of replication-competent HBV DNA in the liver despite a negative blood test for hepatitis B surface antigen (HBsAg). Due to the incompletely-known mechanisms underlying its occurrence and the limitations of existing screening technologies, the viral loads in the blood of OBI patients are intermittent and often undetectable. Furthermore, lack of effective screening and shielding strategies in blood collection and supply institutions fail to prevent OBI individuals from donating blood, resulting in its susceptibility to transmission through blood transfusion, which poses a significant threat to blood safety. In this review, we summarize current understanding of OBI, challenges, and its implication in blood safety.